G93(P) Does the TEN4 clinical decision rule distinguish bruises from physical abuse from inherited bleeding disorders and accidental injury?. (May 2019) - Kemp, AM; Maguire, S; Farewell, D; Nuttall, D; Collins, P; Dunstan, F
Abstract : Aims: The TEN4 rule (bruising to the Trunk, Ear, Neck or in a child <4 months old) is used to identify bruises that warrant a physical abuse (PA) evaluation. We aim to determine whether TEN4 can distinguish PA from accidental injury or inherited bleeding disorders (IBD). Methods: Between 2003–2012, bruising patterns on three groups of children (<6 years) were ascertained, with developmental stage divided into pre-mobile and mobile (crawling, cruising, walking). PA: single recording of bruises at presentation for assessment, PA confirmed by multidisciplinary child protection team. Weekly recordings of all bruises for ≤12 weeks on IBD cases from six haemophilia centres, and children in the community, without child abuse concerns (accidental bruise=controls).Statistical analysis included a multilevel Poisson regression to analyse and quantifying how the average number of bruises in the TEN locations vs.the rest of the body varied with study group and developmental stage. We fitted generalised linear mixed models with a log link function (software R) and used likelihood ratios(LR) to summarise the results. Results: There were 781 children (350 PA, 103 IBD, 328 controls). Bruising frequency at any location increased with increasing mobility, and both PA and IBD children had a greater frequency and greater number of bruises than controls. In pre-mobile children one or more bruise in any location had >5 times the likelihood of PA and >7 times of IBD than controls, the more bruises that a child had, the greater the likelihood of PA/IBD. Pre-mobile children who had a bruise in the TEN location were significantly more likely to have PA than have IBD. Once mobile children had more than one bruise including one in a TEN location the likelihood of PA/IBD was higher than controls (LR PA >2.5, IBD >3.3). In children with multiple bruises (>2), children with a 'TEN' bruise were twice as likely to be PA than IBD. Conclusions: Application of the TEN4 rule is effective at indicating pre-mobile children and mobile children with multiple bruises that warrant further investigation. However, as it is poorer at discriminating between IBD and abuse cases, all those children who score positively must have a coagulation screen in addition to child abuse evaluation.